KONTRIBUSI FAKTOR DEMOGRAFI DAN PEMIKIRAN TERHADAP KARAKTER KEWIRAUSAHAAN MAHASISWA (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThis study aims to contribute each student demographic factors (District of origin, ethnicity, birthplace of father and mother, the father and mothers education, todays parents residence, birth order, parental income, occupation father and mother, marital status of parents, and where to stay in college) against the idea of entrepreneurship courses and student entrepreneurial character. So, is there a correlation of thought to the entrepreneurial character of students, and are there are contributions to the entrepreneurial character of students in Faculty of Teacher Training and Education Science University of Riau. The research sample is determined based on the representation of the 12 districts/cities in Riau Province and 16 courses and includes 4 levels of the semester, a total of 192 people. Data were collected by questionnaire with five options. Data were analyzed using descriptive statistics and inference. Results of the study explained that on 13 demographic factors studied students gained an average contribution to the thinking of students to entrepreneurship courses was 19.84 percent. Onwards, to the entrepreneurial character of the student contribution is 12.76 percent. Based on the results of correlation between thinking with the entrepreneurial character of students, is rxy = 0.688, P<0.01, then this indicates that there is a significant relationship between the thinking of students to entrepreneurship courses to students with the entrepreneurial character of high strength of the relationship. Retrieved students also contribute ideas to the entrepreneurial character of students is 47.30 percent. The results could have implications for the growing need for entrepreneurship courses given to student teachers as a whole, so that later they can be transforming to students in schools where they served as teachers later.Keywords: demographics, student, character, entrepreneurship.